Evaluating the Effectiveness of Chlorhexidine in Reducing Methicillin-Resistant Staphylococcus Aureus (MRSA) Contamination in Nebulizer Equipment - Wisnasari, Shila; Ariningpraja, Rustiana Tasya; Lestari, Retno; Ahsan, Ahsan; Effendy, Nuraeni (Universitas Tribhuwana Tunggadewi, 2025)
Methicillin-resistant Staphylococcus aureus (MRSA) is a significant healthcare-associated pathogen, capable of spreading through contaminated aerosols generated by medical equipment such as nebulizers. The increasing prevalence of MRSA infections, coupled with challenges in effective disinfection, highlights the urgency of identifying optimal disinfection methods. This study aims to assess the effectiveness of chlorhexidine in reducing MRSA contamination in nebulizer equipment, focusing on determining the optimal concentration for disinfecting nebulizers to minimize airborne transmission. This study employed an in vitro experimental design. The study population consisted of MRSA isolates obtained from clinical sputum specimens. The samples included nebulizer equipment inoculated with MRSA suspensions standardized to 10⁷ CFU/mL. Disinfection was carried out using chlorhexidine at concentrations of 2.5%, 4%, and 5%, each diluted in 70% alcohol. Control groups were rinsed with sterile saline and 70% alcohol. Post-disinfection, the nebulizer surfaces were swabbed and cultured on Mueller-Hinton agar to quantify colony-forming units (CFUs). Data were analyzed using paired t-tests and one-way ANOVA followed by Tukey’s post-hoc test, with a significance level set at p 0.05. The results show that chlorhexidine 2.5% reduced bacterial counts to an average of 1 CFU/plate, and 4% chlorhexidine reduced it to 49 CFU/plate. Chlorhexidine 5% resulted in an average of 1,430.6625 CFU/plate. Statistical analysis revealed significant reductions with 2.5% and 4% chlorhexidine compared to controls (p0.01), whereas 5% Chlorhexidine did not show a significant difference. These findings suggest that lower concentrations of chlorhexidine may be sufficient for effective disinfection in nebulizer equipment, addressing the risk of MRSA spread through airborne particles.